Teaching critical reading in schools and associate with education - Güneş, Ayşenur; Güneş, Fatih (Qualitative and Quantitative Methods in Libraries; Vol 3 No 4 (2014): December 2014 Issue, 2017)
In this study, increase student’s success level in education and emphasize the importance of critical reading in order to create positive developing in viewpoint with increase their level of consciousness. Also requirement about gain this ability and habit in education process is explain. In this context, reading habit, critical reading education and effect critical reading to education life are examined. This study’s subject is about, contribution of critical reading ability’s to students education life. In this study thought that,  when student gain the critical reading habit and using it in everyday life, their education’s effect are increase. In this context, to attract attention; critical reading’s importance in education and teaching it with education.